Pengaruh Penambahan Ekstrak Akar Manis (Glycyrrhiza glabra L.) terhadap Aktivitas Antibakteri Permen Eritritol - Salaf, Azizah Almisykatu; Sarbini, Dwi; Purwani, Eni (Universitas Tadulako, 2025)
Dental caries is a chronic infectious disease that remains a major global health problem, primarily caused by Streptococcus mutans, a bacterium capable of forming dental biofilms. Preventive strategies can be developed through the use of natural non-cariogenic agents such as erythritol which exhibits anti-biofilm properties and licorice root (Glycyrrhiza glabra L.), which contains antibacterial compounds including flavonoids and saponins. This study aimed to evaluate the in vitro antibacterial potential of erythritol candy supplemented with licorice root extract against Streptococcus mutans. The study employed a Completely Randomized Design (CRD) consisting of four treatments with different concentrations of licorice root extract (0%, 2%, 3%, and 5%), along with a positive control (ampicillin) and a negative control (distilled water). Antibacterial activity was assessed using the well diffusion method and the inhibition zone diameters were analyzed statistically using Kruskal–Wallis test. The results showed that increasing the concentration of licorice root extract tended to enhance antibacterial activity with inhibition zones ranging from 1.00 ± 0.70 mm (2%) to 3.25 ± 1.76 mm (5%), although the differences were not statistically significant (p > 0.05). In conclusion, erythritol candy containing licorice root extract demonstrated potential antibacterial activity against Streptococcus mutans, although the effect was relatively weak. Further studies are recommended to determine the Minimum Inhibitory Concentration (MIC), evaluate anti-biofilm activity, and conduct in vivo testing to confirm its effectiveness under physiological conditions.